STRATEGI KOMUNIKASI DALAM PENYULUHAN PERTANIAN DENGAN M VENDOR (SUATU PENDEKATAN KOMUNIKASI KELOMPOK & INTAPERSONAL) - EKO MURDIYANTO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2010)
Agricultural counseling process as a locomotive in spreading new technology to farmers has developed quickly since the introduction of several communication models, This quick development was also supported by development of counseling institutions and agricultural agents.